Ethno-Pedagogical Module: A Theoretical Exploration of Knowledge Transmission in Ethnobiological Systems - Rexhepi, Besnik; Bajrami, Ani (International Journal of Environment, Engineering and Education, 2025)
The vertical transmission of ethnobiological knowledge across generations is crucial in preserving biodiversity and sustaining biocultural diversity. However, the mechanisms underpinning this process remain insufficiently studied. This paper introduces the "ethno-pedagogical module" as a novel interdisciplinary framework for analyzing and enhancing the understanding of traditional ecological knowledge (TEK) transmission. The module integrates perspectives from cultural anthropology, education theory, and ethnobiology. Cultural anthropology contributes insights into the role of rituals, oral traditions, and communal practices in knowledge dissemination. Education theory offers methodologies for understanding experiential and participatory learning processes essential to TEK. Ethnobiology provides the foundation for examining the practical and symbolic human-environment relationships embedded in traditional practices. This framework facilitates the disaggregation of TEK systems and enables cross-cultural comparisons, revealing how diverse communities sustain biocultural diversity through unique adaptive practices and learning processes. It also offers practical applications by guiding the integration of TEK into formal and informal education systems to foster environmental stewardship and cultural resilience among younger generations. By addressing the complexities of TEK transmission, the ethno-pedagogical module presents a structured approach for preserving traditional knowledge amidst global environmental and cultural changes. The module bridges traditional ecological practices with contemporary educational strategies, promoting resilience and innovation in sustaining biocultural diversity. This interdisciplinary approach underscores the importance of collaboration in safeguarding cultural heritage and biodiversity in an increasingly interconnected and rapidly changing world.